THE STUDY OF SPEECH ACT ON LUCY MAUD MONTGOMERY’S NOVEL TITLED ANNE OF GREEN GABLES - Dewi, Citra; Farlina, Nina (JURNAL LITERARY CRITICISM, 2014)
This research titled is ?The Study of Speech Act on Lucy Maud Montgomery?s Novel Titled Anne of Green Gables?. The purpose of this research is to analyze speech acts and meaning based on Austin terms that found on dialogue on novel story line. Research method is research library and supported by all information on internet. Speech act is a symptom of communication process and according to Austin divided into three categories, locutionary, illocutionary and perlocutionary. The type of speech act that the most used in Anne of Green Gables novel is illocutionary of order. The researcher also analyzing the meaning of speech act from the speaker views and the hearer views and the effect of perlocutionary from each dialogues.Keywords: speech act, Anne of Green Gables, locutionary, iIllocutionary, perlocutionary